Evaluation of antidiabetic and antioxidant activity of methanolic extract of Limonia acidissima leaves in alloxan-induced diabetic wister albino rats: a randomized controlled experimental study - Baheti, Ashishkumar; Chimurkar, Leena; Mohod, Kanchan (Creative Pharma Assent, 2023)
Objectives: The present study was carried out to find graded-doses antidiabetic and antioxidant activities of methanolic extract of Limonia acidissima (MELA) leaves in rats. Materials and Methods: Male Wistar rats were randomly divided into 6 groups (n=8): Normal control, Diabetic control (Alloxan-induced), and test groups where varying doses of MELA (100mg/kg, 200mg/kg, and 400mg/kg) or Metformin (100mg/kg) administered post-alloxan induction. Random blood sugar (RBS) levels were estimated at specific intervals over a 28-day period. Moreover, antioxidant markers (malondialdehyde, superoxide dismutase, and reduced glutathione) were assessed on day 28. Histopathological examination of pancreatic tissue was conducted. Results: Overall, mean RBS levels decreased at all intervals. There was a significant decrease in median malondialdehyde, an increase in median superoxide dismutase, and reduced glutathione levels (all p-values<0.0001). The change in RBS (p-values<0.0001) and antioxidants (p-value>0.05) levels was greater in Group VI than in Group V. On histopathology, Groups VI and V demonstrated regeneration of necrotic β-cells in the islets, and this was more pronounced than Group IV. Conclusion: Results of our study suggested that MELA possesses dose-dependent significant antidiabetic and antioxidant activity.